Pendampingan Proses Penyembelihan dan Pendistibusian Hewan Qurban tahun 1444 Hijriah pada 5 Lokasi di Kabupaten Tangerang - winanti, winanti; Himmy'azz, Istajib Kulla; Kumoro, Dwi Ferdi Cahya; Purno, Marhaendro; Suwita, Jaka; Nurasiah, Nurasiah; Yulia, Yayah; Hasna, Shofwatun; Basuki, Sucipto (IAHN Gde Pudja Mataram, 2023)
Assistance is carried out in the four assisted villages and communities around the campus by involving lecturers and students. Assistance activities are carried out to educate and understand the community in slaughtering, procedures, Eid al-Adha lessons, criteria for sacrificial animals and distribution of sacrificial animals according to syar'i. Not all animals can be used as sacrificial animals, but there are provisions that must be considered in sacrificing. In addition to the mentoring activities, the campus also handed over one sacrificial cow as well as a cutting fee to help the community in the target village and the community around the campus.